Pengaruh Pelatihan, Kepuasan Kerja dan Kompetensi terhadap Kinerja Karyawan Usaha Kecil Menengah - Dorris Yadewani (Universitas Bumigora, 2023)
The research conducted on small and medium enterprises Tahu ATB in Padang, aims to analyze the effect of training on employee performance, analyze the effect of job satisfaction on employee performance and analyze the effect of competence on employee performance. The population of this study were all employees, namely as many as 10 people, the sampling technique was using a census technique. Data analysis techniques using multiple regression and hypothesis testing using SPSS 26. The results of this study are training has a significant effect on employee performance, competence has a significant effect on employee performance and job satisfaction has a significant effect on employee performance.